2003
DOI: 10.1136/jmg.40.5.325
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the neuronal PAS3 gene in a family affected with schizophrenia

Abstract: Schizophrenia and its subtypes are part of a complex brain disorder with multiple postulated aetiologies. There is evidence that this common disease is genetically heterogeneous, with many loci involved. In this report, we describe a mother and daughter affected with schizophrenia, who are carriers of a t(9;14)(q34;q13) chromosome. By mapping on flow sorted aberrant chromosomes isolated from lymphoblast cell lines, both subjects were found to have a translocation breakpoint junction between the markers D14S730… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
116
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 27 publications
4
116
0
1
Order By: Relevance
“…It appears that the brain transcription factor neuronal PAS domain protein 3 (NPAS3) is affected by the translocation and thus has a possible role in the manifestation of psychotic symptoms. 61,72 For other genes on this chromosome, V-AKT murine thymoma viral oncogene homolog 1 (AKT1), an arbitrator of neuronal survival in the developing brain, is a promising vulnerability gene. 14 …”
Section: Chromosome 11mentioning
confidence: 99%
“…It appears that the brain transcription factor neuronal PAS domain protein 3 (NPAS3) is affected by the translocation and thus has a possible role in the manifestation of psychotic symptoms. 61,72 For other genes on this chromosome, V-AKT murine thymoma viral oncogene homolog 1 (AKT1), an arbitrator of neuronal survival in the developing brain, is a promising vulnerability gene. 14 …”
Section: Chromosome 11mentioning
confidence: 99%
“…14 In a spatiotemporally controlled manner in the cerebellum, nuclear expression has also been identified in basket cells and in Bergmann's glia, with some cytoplasmic staining evident in the internal granule layer of neurons. 14 After initial cloning of the NPAS3 gene, 13 the objective of the present study was to investigate the role of this gene in diseases in human beings. Previous studies have suggested a potential role of NPAS3 in congenital neurobehavioral and neurodevelopmental anomalies.…”
mentioning
confidence: 99%
“…Neuronal PAS domain-containing protein 3 (NPAS3) is another worth noting gene with susceptibility of schizophrenia [85]. NPAS3 is a basic helix-loop-helix transcription factor which was discovered in a family that suffered from schizophrenia [85].…”
Section: Neurogenesis and Schizophreniamentioning
confidence: 99%
“…NPAS3 is a basic helix-loop-helix transcription factor which was discovered in a family that suffered from schizophrenia [85]. Transgenic mice with NPAS3 mutation showed a behavioral phenotype with reduced memory, impaired social recognition and impaired sensorimotor gating [86], which are also characteristics of schizophrenic patients.…”
Section: Neurogenesis and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation